2019
DOI: 10.1038/s41598-019-51466-5
|View full text |Cite
|
Sign up to set email alerts
|

HOMA-estimated insulin resistance as an independent prognostic factor in patients with acute pancreatitis

Abstract: This prospective study investigated the relationship between insulin resistance assessed using the homeostatic model assessment of insulin resistance (HOMA-IR) and the prognosis of acute pancreatitis (AP). A total of 269 patients with AP were recruited in this study. HOMA-IR scores were calculated using fasting insulin and plasma glucose levels. Patients were then categorized into the non-insulin-resistant group (HOMA-IR <2.5) and the insulin-resistant group (HOMA-IR ≥2.5). We performed multivariable logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…Insulin resistance is the hallmark of DM. 25 Seung Kook Cho demonstrated that insulin resistance assessed using Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) was significantly associated with severity of pancreatitis and Intensive Care Unit admission. 25 Ali Riza Koksal et al found insulin levels were statistically significantly higher in patients who developed PEP than in the ones who did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance is the hallmark of DM. 25 Seung Kook Cho demonstrated that insulin resistance assessed using Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) was significantly associated with severity of pancreatitis and Intensive Care Unit admission. 25 Ali Riza Koksal et al found insulin levels were statistically significantly higher in patients who developed PEP than in the ones who did not.…”
Section: Discussionmentioning
confidence: 99%
“…25 Seung Kook Cho demonstrated that insulin resistance assessed using Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) was significantly associated with severity of pancreatitis and Intensive Care Unit admission. 25 Ali Riza Koksal et al found insulin levels were statistically significantly higher in patients who developed PEP than in the ones who did not. 26 This current study reveals, PEP is significantly more in people with DM getting insulin than in people without insulin (p value 0.046).…”
Section: Discussionmentioning
confidence: 99%
“…Concluding that insulin resistance is potentially involved in the mechanism for severe AP. 12 Concerning these findings, it has been found that various pro-inflammatory factors or cytokines are activated due to insulin resistance, including nuclear factor-kB, 13 tumor necrosis factor-alpha, 14 amylin, 15 and interleukin-6, 16 and these pro-inflammatory factors may be responsible for the initiation and progression of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of IL-6 has been also shown in experimental models of AP where it is associated with enhanced local and systemic response. The association between IR and AP severity was investigated in a prospective clinical study, where IR was shown to be an independent factor in predicting AP severity (62). These data suggest that in addition to increasing the risk of diabetes development, IR also exacerbates the outcome of pancreatitis.…”
Section: Post-acute Pancreatitis Diabetes Mellitusmentioning
confidence: 99%